The Influence of Digital Marketing, Promotion and Product Innovation on The Marketing Performance of MSMEs in Cikarang - Windi; Yahya, Adibah; Kartika, Dewi (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the influence of digital marketing, promotion, and product innovation on marketing performance among MSMEs in the Cikarang region. The research is motivated by the significant growth in the number of MSMEs, which has intensified competition and demands the application of effective marketing strategies. A quantitative associative method was employed, using purposive sampling and data analysis through Structural Equation Modeling (SEM) with the SmartPLS 3.0 software. The results indicate that digital marketing and promotion have a significant influence on marketing performance, whereas product innovation does not show a significant effect. Therefore, MSME actors are advised to enhance the use of digital media and develop more innovative promotional strategies, while also reevaluating product innovation efforts to better align with market needs. The statistical analysis using SmartPLS revealed that digital marketing (t = 2.223, p < 0.05) and promotion (t = 2.326, p < 0.05) significantly affect marketing performance, while product innovation does not (t = 0.205, p = 0.837). The R² value of 0.728 indicates that 72.8% of the variance in marketing performance is explained by the model, suggesting a strong predictive capability. The study also suggests that future research consider additional variables such as product quality, pricing, and customer service to achieve more comprehensive findings.